KUALITAS DAGING SAPI DENGAN KEMASAN PLASTIK PE (Polyethylen) dan PLASTIK PP (Polypropylen) DI PASAR ARENGKA KOTA PEKANBARU - Hafri Yanti; Hidayati Hidayati; Elfawati Elfawati (State Islamic University of Sultan Syarif Kasim Riau, 2008)
The objective of this study was to know the influence of two kinds of plastic packing, i.e. Polyethylen (PE) and Polypropylen (PP), for total plate count, moisture, crude protein, pH I;Uld cooking loss of the fresh meat. The experiment was designed using completely randomized block design with three treatments of packaging (Le. unpacking as control, PE plastic packing and PP plastic packing) and three blocks of sampling day. The result showed that the packaging using PE and PP plastics decreased bacteria contamination, moisture, pH, cooking loss and maintained of crude protein of the fresh meat. The PP plastic better than the PE plastic in maintain themeat quality.